Competition alters life history and increases the relative fecundity of crop-wild radish hybrids (Raphanus spp.) - Campbell, Lesley G (The New phytologist, 2007)
The evolutionary impact of crop-to-wild gene flow depends on the fitness of hybrids under natural, competitive conditions. Here, we measured the performance of third-generation (F3) radish hybrids (Raphanus raphanistrum x Raphanus sativus) and weedy R. raphanistrum to understand how competitive interactions affect life history and relative fecundity. Three wild and three F1 crop-wild hybrid radish populations were established in semi-natural, agricultural conditions in Michigan, USA. The effects of competition on life-history traits and fecundity of F3 progeny were measured 2 yr later in a common garden experiment. Third-generation hybrid plants generally produced fewer seeds per fruit and set fewer fruits per flower than wild plants, resulting in lower lifetime fecundity. With increasing competition, age at reproduction was delayed, the relative number of seeds per fruit was reduced in wild plants and differences between hybrid and wild fecundity diminished. Competition may enhance the fecundity of advanced-generation hybrids relative to wild plants by reducing differences in life history, potentially promoting the introgression of crop alleles into weed populations